Implementasi e-modul berbasis proyek untuk meningkatkan aktivitas dan hasil belajar mahasiswa STKIP Qomaruddin Gresik - Muhammad Jamaluddin; Roisatun Nisa' (Math Didactic: Jurnal Pendidikan Matematika, 2018)
This research was conducted on students of Mathematics Education Program of STKIP Qomaruddin Gresik. It aimed at increasing student activity and learning outcomes through e-modul based project. This type of research is Action Research with research subjects were students who take mathematics learning evaluation system courses. To collect the data, this reasearch used observation and projects. The results showed that student activity and learning outcomes increased. The increase can be seen from the comparison of learning activity scores for students in cycle I and cycle II. In the action phase of cycle I, 64% students were classified as very good, 36% students were classified as good, in the second cycle action there were 73% students were classified as very good, 27% students were classified as good. The Improvement of assessment result can be seen from the comparison of learning outcomes in cycle I and cycle II. In the first phase of the action I, 55% students were classified as very complete, 41% students were classified as complete, and as many as 4% student were classified as incomplete. In the second phase of the action phase, 64% students were classified as very complete, as many as 36% students were classified as complete.